Pharmaceutical assistance in pregnant women with gestational Diabetes mellitus (Research, Society and Development, 2023)
Introduction: According to the World Health Organization, Gestational Diabetes Mellitus is a metabolic dysfunction whereby there is an intolerance to carbohydrates of varying severity. Several studies have pointed out that this dysfunction is very common during pregnancy, affecting approximately 3 to 25% of pregnant women. Objective: To analyze the main aspects involving gestational diabetes and identify the role of the pharmacy professional in this case. Methodology: This work is a descriptive and exploratory study based on a literature review, conducting research and collecting scientific data organized through the investigation of articles associated with the object of study. Expected Results: GDM poses risks to the mother, fetus and newborn, usually diagnosed in the 2nd or 3rd trimester. It may be transient or persist after delivery, being characterized as an important risk factor for the development of Type 2 Diabetes Mellitus. The prevalence ranges from 1% to 14%, depending on the population studied and the diagnostic criteria used. Final considerations: Metformin, which is an oral hypoglycemic drug indicated mainly for the treatment of gestational diabetes mellitus, acts by reducing blood sugar levels to levels closer to normal. Pharmaceutical care promotes the recovery of health integrated with rational use of medications in order to improve the patient's quality of life, in relation to non-pharmacological measures, the pharmacist during Primary Care (AT) for pregnant women can advise on health actions aimed at improving the patient's quality of life.